2021
DOI: 10.1002/adma.202007949
|View full text |Cite
|
Sign up to set email alerts
|

Bioengineering Approaches for the Advanced Organoid Research

Abstract: organoids should exhibit essential features, including organ-specific multiple cell types, functions of the organ, and spatially organized structures. The emergence and progression of organoid technologies have resulted from several important discoveries (Figure 1). The formation of actual tissuelike colonies in vitro was firstly observed from a co-culture system of keratinocytes and 3T3 fibroblasts. [4] Self-organization, one of the fundamental aspects of organogenesis, was first observed via two distinct app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
61
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(65 citation statements)
references
References 235 publications
0
61
0
Order By: Relevance
“…Fabricating a microenvironment that mimics physiological settings, such as incorporating bioactive drugs into the bioprinting process, [ 19 ] or introducing them into the culture of the construct post‐printing determines the regenerative outcomes. [ 20 ] To date, a number of biochemical cues, including the growth factors (e.g., transforming growth factors, bone morphogenetic proteins, and insulin‐like growth factor‐1); small bioactive molecules (e.g., E7 peptide and kartogenin [KGN]); biophysical factors (e.g., chondroitinase ABC and lysyl oxidase‐like 2); and gene therapy, have been demonstrated that could significantly improve the regeneration of osteochondral tissue. [ 19a,21 ] However, due to the lack of drug‐loading groups, the conventional hydrogel bioinks such as GelMA and MeHA generally suffer from the burst release of bioactive drugs where the sustained release of a low dose is favorable for the effective regeneration of osteochondral defects.…”
Section: Introductionmentioning
confidence: 99%
“…Fabricating a microenvironment that mimics physiological settings, such as incorporating bioactive drugs into the bioprinting process, [ 19 ] or introducing them into the culture of the construct post‐printing determines the regenerative outcomes. [ 20 ] To date, a number of biochemical cues, including the growth factors (e.g., transforming growth factors, bone morphogenetic proteins, and insulin‐like growth factor‐1); small bioactive molecules (e.g., E7 peptide and kartogenin [KGN]); biophysical factors (e.g., chondroitinase ABC and lysyl oxidase‐like 2); and gene therapy, have been demonstrated that could significantly improve the regeneration of osteochondral tissue. [ 19a,21 ] However, due to the lack of drug‐loading groups, the conventional hydrogel bioinks such as GelMA and MeHA generally suffer from the burst release of bioactive drugs where the sustained release of a low dose is favorable for the effective regeneration of osteochondral defects.…”
Section: Introductionmentioning
confidence: 99%
“…The construction strategy of organoids is based on the multipotent differentiation and the self-renewal capacity of stem cells. With a deeper understanding of ECM, 3D culture technology can be an effective tool for the structural support of organoids, and the construction methods are diverse and may be customized [ 39 ]. Recently, a range of growth factors and small molecules which simulate the microenvironment of tissue-related stem cells during the process of organogenesis have been revealed.…”
Section: Discussionmentioning
confidence: 99%
“…One ultimate goal of organoid technology is to construct a bio-smart organoid, which can be well-integrated with native tissues to repair damaged organs. In order to better explore the potential application of organoids, scientists should make further efforts in the development of advanced bio-smart materials together with a deeper understanding of stem cell biology [ 39 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, new advances in biomaterial engineering are moving towards an increasing capacity to faithfully recapitulate the heterogeneity of the tumor ECM [ 102 ]. The use of new biomaterials for LCO technology will likely benefit from the advances in 3D culture protocols for normal organoids from lung or other tissues [ 87 , 103 ]. In this regard, a recent report described the use of hyaluronic acid hydrogels for the generation and expansion of iPSC-derived lung alveolar organoids, achieving an increased homogeneity in organoid size and structure [ 104 ].…”
Section: Future Directions and Conclusionmentioning
confidence: 99%